Agroecological state and ways of increasing soil fertility of “E. V. MAlev’s” PFE of the Giaginsky district of the Republic of Adygeya - I. E. Sinelnikova; B. S. Tsipinova (Новые технологии)
The Giaginsky region has valuable soil resources. The main task of each farm in the region is to increase the yield of cultivated crops and increase their total volume. This is possible with the rational use of lands, fertilizers, introduction of new technologies soil processing soil, protecting them from erosion. For successful and effective application of these measures, it is necessary to study the soil cover of individual farms and the region as a whole.